“Da natural vaghezza mosso”:Giovanni Francesco Gemelli Careri’s Travels Through Armenia (1694) - Boschis, Alessia
Travel Literature is a goldmine of information for the study of Armenian art and culture. Nevertheless, it is a largely unexplored field of investigation, especially accounts written in Italian. Among the understudied works, Giro del mondo (1699-1700) by Giovanni Francesco Gemelli Careri (1651-1724) stands out. Travelling to Ispahan across Historical Armenia in 1694, Gemelli described populations, settlements, and monuments. The analysis retraces the traveller's path examining the information on the presence and conditions of the Armenian artistic heritage.
Keywords: Armenian art